Failing to level up? Industrial policy and productivity in interwar Northern Ireland - David Jordan (Queen's University Centre for Economic History (QUCEH), 2023)
Northern Ireland's productivity performance has persistently been the worst of any UK region. This is despite having the apparent benefit of subnational industrial policy since the 1920s. Can institutions - through the interaction between business and local policymakers - explain this longstanding productivity gap? Existing literature focuses on post-war policy in Northern Ireland, but neglects its interwar origins. Using new comparisons of regional and sectoral industrial productivity, and new archival evidence for Stormont's interwar industrial policy, demonstrates regional institutions created barriers to productivity growth, restricting the development of new industries in Northern Ireland. Further UK devolution will not automatically promote regional convergence: its success will depend upon the institutional incentives faced by subnational policymakers.
Keywords: H20; N64; O43; R50; 330; productivity; industrial policy; institutions; devolution; interwar manufacturing